When Does Teacher Support Reduce Depression in Students? The Moderating Role of Students' Status as Left-Behind Children - Li, Wei; Gao, Wen yang; Fu, Wei dong (Frontiers in Psychology, 2021)
Teacher support (TS) makes students feel loved and cared for because they believe that their teachers will provide them with opportunities to make choices, support them in independent problem solving, and understand their inner feelings. High TS levels reduce depression and anxiety, thereby improving students’ mental well-being. This cross-sectional study involved 3,573 students from 29 schools in 16 counties/cities of six provinces, namely Guizhou, Hubei, Jiangxi, Shanxi, Sichuan, and Yunnan. The aim was to examine the impact of TS on students’ level of depression. The results indicated that for children in elementary schools, their status as left-behind children (LBC) played a moderating role between TS and depression. The level of depression in non-LBC children decreased significantly with increases in TS, but the reduction for LBC children was not significant. For children in middle/junior high schools, their LBC status did not play a moderating role between TS and depression. TS was negatively correlated with the children’s level of depression, but there was a significant positive relationship between their LBC status and depression. The theoretical and practical significance of the research findings were further discussed.